A integração das tecnologias educacionais na prática pedagógica do componente curricular de educação física no ensino médio de uma escola pública - Morisso, Maríndia Mattos (2017)
The presence of technologies in education has grown considerably in recent years. Thus, discussions on how to integrate technological tools into pedagogical practice have increased in the academic world. Physical Education, because it is a compulsory curricular component of basic education, is also part of these concerns. In this sense, this research sought to investigate the challenges and potentialities of the integration of educational technologies in the pedagogical practice of the curricular component of Physical Education in the high school of a public school. For this, we conducted a qualitative approach action research. The work consisted in developing together with a cooperating teacher a cyclical process of actionreflection- action. The instruments used were participant observation, which developed from the monitoring of planning and classes, as well as semi-structured interview at the end of the survey, in order to evaluate the entire process. The data were analyzed based on the triangulation of information obtained from the study meetings with the teacher, monitoring the interaction of the online participants and observations of the classes. From this, we present the results of the study according to the steps of the action research: Observation - problem identification; Reflection and planning for improvement and innovation of pedagogical practice; Implementation of planning and observation; Evaluation of changes. We interpret that the integration of educational technologies in the pedagogical practice of Physical Education offers contributions to the teaching-learning process. The technologies provide greater interaction between teacher-student and student-student in tasks that are performed in virtual environments, motivates the students to participate in a collaborative way of group activities and allows more production of knowledge about the body culture of movement both by students and by the teacher. However, we observed that this movement is interfered with by some factors that make it difficult to take advantage of resources as: Low technological fluency, Technologies that don’t work and a little time for the teacher to interact. The data produced during the realization of this research made it possible to interpret that integrating the educational technologies in the classes of Physical Education can be considered an innovative movement, in this sense, We understand that as action research we produce an important change. However, the innovation will only continue if the teacher establishes collaboration networks in which she feels recognized for her work.